Age-related effects of smoking on culprit lesion plaque vulnerability as assessed by grayscale and virtual histology–intravascular ultrasound. Issue 6 (September 2015) - Kang, Soo-Jin; Mintz, Gary S.; Witzenbichler, Bernhard; Metzger, D. Christopher; Rinaldi, Michael J.; Duffy, Peter L.; Weisz, Giora; Stuckey, Thomas D.; Brodie, Bruce R.; Shimizu, Takehisa; Litherland, Claire; Kirtane, Ajay J.; et al.
<x xml:space="preserve">Abstract</x> Background Although smoking is a risk factor for coronary atherosclerosis, the age-related impact on lesion characteristics and plaque instability remains unclear. Patients and methods In ADAPT-DES, 780 patients with 916 culprit lesions were evaluated by preprocedural grayscale and virtual histology–intravascular ultrasound. Results Current smokers (smoking within 1 month) more often presented with acute coronary syndrome (67 vs. 51 vs. 51%, P<0.05) compared with former smokers (no smoking for >1 month) or nonsmokers. In patients 65 or more years of age, current smokers (vs. nonsmokers) showed larger normalized volumes of plaque and media [8.6 (7.8–9.4) vs. 7.2 (6.8–7.7) mm3/mm, P=0.016] and external elastic membrane [14.4 (13.2–15.5) vs. 12.8 (12.2–13.4) mm3/mm, P=0.05]. At the minimal lumen area site, despite a greater plaque burden, the larger external elastic membrane area [14.4 (13.1–15.7) vs. 12.0 (11.3–12.7) mm2, P=0.003] contributed toward preserving the minimal lumen area [2.6 (2.4–2.7) vs. 2.6 (2.5–2.7) mm2, P=0.91] in current smokers (vs. nonsmokers) 65 or more years of age. Moreover, current smokers (vs. nonsmokers) 65 or more years of age showed a greater normalized necrotic core volume [1.19 (0.96–1.46) vs. 0.75 (0.66–0.85) mm3/mm, P=0.0007], more thin-cap fibroatheromas (61 vs. 48%, P=0.04), and plaque ruptures (38 vs. 26%, P=0.051). Conversely, in patients younger than 65 years of age, there was no significant difference in culprit lesion morphology among current, former, and nonsmokers. Conclusion In patients 65 or more years (not in patients<65 years), smoking increased culprit lesion plaque instability (greater plaque with more necrotic core, thin-cap fibroatheromas, positive remodeling, and plaque ruptures).